The personality of Krystal Weedon in J.K Rowling’s the casual vacancy : a psychoanalysis study - Sutrisno, Selvie M.S. (Universitas Ahmad Dahlan, 2021)
The writer discuss about the personality of the main character, Krystal Weedon, in The Casual Vacancy. The writer focuses on the personality of Krystal Weedon by using psychoanalysis approach. In this research, the writer used qualitative research method. Quality refers to the what, how, when, and where of a thing its essence and ambience. This novel described a unique personality of Krystal Weedon as a teenager that has many problems in her life. By means of the background above, the writer would like to analyze the novel The Casual Vacancy using psychoanalysis study to reveal the personality of the main character in this novel.